2013
DOI: 10.1074/jbc.m112.449033
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Tail Loss Is an Evolutionary Mechanism for Liberating Marapsins and Other Type I Serine Proteases from Transmembrane Anchors

Abstract: Background: Vertebrate marapsins can be either type I transmembrane proteases or unanchored. Results: Point mutations liberated marapsins from transmembrane peptides independently in human-related primates and other mammalian clades. Soluble marapsins are active and inhibitor-resistant. Conclusion: Mutational tail loss transformed transmembrane marapsins and related proteins into soluble proteases. Significance: These findings suggest a general evolutionary mechanism for evolving proteases with new properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Of these, several have already been knocked out in the mouse. It was determined that Prss16, Prss27, Prss35, and Tmprss4 have no abnormal phenotype [25][26][27] and Prss1, Prss8, Prss12, Prss56, Tmprss2, Tmprss3, Tmprss6, Tmprss11a, and Tmprss13 have non-reproductive phenotypes [27][28][29][30][31][32][33][34][35]. Although a functional requirement for Prss41 has not been determined through a mouse model, it has been shown to be testis-specific, predominantly expressed in the plasma membrane of spermatogonia and Sertoli cells in the basal compartment, and exhibits an intracellular localization in spermatocytes and spermatids in the adluminal compartment of the seminiferous tubules [36].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, several have already been knocked out in the mouse. It was determined that Prss16, Prss27, Prss35, and Tmprss4 have no abnormal phenotype [25][26][27] and Prss1, Prss8, Prss12, Prss56, Tmprss2, Tmprss3, Tmprss6, Tmprss11a, and Tmprss13 have non-reproductive phenotypes [27][28][29][30][31][32][33][34][35]. Although a functional requirement for Prss41 has not been determined through a mouse model, it has been shown to be testis-specific, predominantly expressed in the plasma membrane of spermatogonia and Sertoli cells in the basal compartment, and exhibits an intracellular localization in spermatocytes and spermatids in the adluminal compartment of the seminiferous tubules [36].…”
Section: Introductionmentioning
confidence: 99%
“…PRSS27 encodes for marapsin, a tryptic serine protease acting on synthetic tetrapeptide substrates but with no general protease activity and with an unusual resistance to inhibitors such as aprotinin, serum serpins, and soybean trypsin inhibitor. 32 It has been suggested that the active site is partially blocked and does not allow access to large substrates and inhibitors. DPP7 (Dipeptidyl Peptidase 7) gene encodes for a serine aminopeptidase that cleaves dipeptides from the N-terminal of proteins that have a proline at the penultimate position.…”
Section: Resultsmentioning
confidence: 99%
“…Although being a transmembrane protein on first inspection would seem to place γ-tryptases into a class of peptidases not closely related to soluble tryptases, phylogenetic analysis suggests that soluble mast cell tryptases evolved from γ-like ancestral transmembrane proteins early in mammalian evolution (Trivedi et al, 2007). In further support of such a transition, the example of marapsin suggests a rather facile, one-step evolutionary pathway for converting a type 1 transmembrane tryptic protease to its soluble homologue (Raman et al, 2013). The standard topology of type I proteins predicts that γ-tryptase is anchored to the inside of the secretory granule lipid bilayer (Caughey et al, 2000a).…”
Section: Tryptasesmentioning
confidence: 97%